The Relationship Between Stressful Study And StudentsÔÇÖ Sleep Pattern During Covid-19 Pandemic - Mulyati, Sri; Sisrazeni, Sisrazeni (Journal of Islamic Education Students (JIES), 2022)
Covid 19 pandemic that required students to study online affected university students psychologically. This study aims to determine the relationship between stressful learning and sleep patterns of Bimbingan dan Konseling department students in Covid 19 pandemic era. Correlational design of quantitative approach was used in this research. Sample was chosen by using saturated sampling technique and data were collected by distributing a Likert scale questionnaire to the sample. Data then were analyzed using Product-moment formula. The finding described that there was a significant relationship between stressful learning and sleep patterns. Thus, the higher the studentsÔÇÖ stress level in learning, the worse the studentsÔÇÖ sleep pattern during Covid-19 pandemic.┬á